2011
DOI: 10.1038/ncomms1453
|View full text |Cite
|
Sign up to set email alerts
|

Parkinson's disease induced pluripotent stem cells with triplication of the α-synuclein locus

Abstract: A major barrier to research on Parkinson's disease is inaccessibility of diseased tissue for study. One solution is to derive induced pluripotent stem cells from patients and differentiate them into neurons affected by disease. Triplication of SNCA, encoding α-synuclein, causes a fully penetrant, aggressive form of Parkinson's disease with dementia. α-Synuclein dysfunction is the critical pathogenic event in Parkinson's disease, multiple system atrophy and dementia with Lewy bodies. Here we produce multiple in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
352
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 418 publications
(376 citation statements)
references
References 60 publications
13
352
0
2
Order By: Relevance
“…2012), Huntington's disease (HD) (HD iPSC Consortium 2012), and Parkinson's disease (PD) (Devine et al. 2011). However, to the best of our knowledge, only one pilot study reported research using human iPSC‐derived neural cells in alcohol abuse (Lieberman et al.…”
Section: Introductionmentioning
confidence: 99%
“…2012), Huntington's disease (HD) (HD iPSC Consortium 2012), and Parkinson's disease (PD) (Devine et al. 2011). However, to the best of our knowledge, only one pilot study reported research using human iPSC‐derived neural cells in alcohol abuse (Lieberman et al.…”
Section: Introductionmentioning
confidence: 99%
“…From each culture of reprogrammed fibroblasts, colonies are selected and are subjected to quality-control measures such as transgene silencing and karyotype analysis. However, these clones, colonies derived from the same human donor, still exhibit large variability (Devine et al, 2011). This can lead to considerable phenotypic variability that is unrelated to their genotype and a differing efficiency to which iPSC lines differentiate into neurons (Sánchez-Danés et al, 2012).…”
Section: Case Reportmentioning
confidence: 99%
“…the role of α-synuclein or LRRK2, etc. ), particularly when the iPSCs are generated from patients with a hereditary form of Parkinson's disease [29,30].…”
Section: Mouse Ipscs As Crucial Model Systemmentioning
confidence: 99%